Increasing concentrations of iron fertilizer affect antibacterial activity of basil (Ocimum basilicum L.) - Gürgan, Muazzez; Adiloğlu, Sevinç (Industrial crops and products, 2021)
•Ocimum basilicum L. can uptake iron from the soil and accumulate in its body.•Two levels of chelated iron change nutrient contents of basil.•Chelated iron application elevated the iron content of the plant.•The antibiotic acitivity of basil extracts decrease with increased iron content. The fertilizer utilization in agriculture may affect the properties of the cultivars which can harm metabolism and affect the health benefits of plants. Medicinal aromatic plants are subject to a great area of utilization all over the world in traditional medicine, cosmetic and pharmaceutical industry. These plants have antioxidant, anticancer, and antibacterial effects due to their bioactive ingredients. Basil (Ocimum basilicum L.) is one of the medicinal plants cultivated around the world. It is rich in antioxidants and phenolic compounds and therefore has inhibitory effect on bacterial growth. The properties of soil affect and alter the nutrient elements and bioactive components of the plants. The agricultural soils are under pollution upon urbanization, industrialization and agricultural practices that may cause accumulation of elements which are normally required for growth and healthy metabolism of plants to a toxic level. In this study the change in macro and micro nutrient contents of basil plant grown in soil with applications of 100 and 200 mg/kg chelated iron were compared with those of the control condition. Moreover, the effect the chelated iron on the antibacterial activity of basil extract was evaluated on Escherichia coli and Staphylococcus aureus with agar well diffusion method as well as the correlation of antibacterial activity with macro and micro elements. The results revealed that basil has an ability to accumulate iron from soil. However, Fe accumulation might have exerted a toxicity on basil and decreased in some micronutrients and impairment in metabolism of basil. Accordingly, increased chelated iron application elevated the iron content of the plant and decreased inhibitory level on both bacteria.